(untitled) (Journal of Informatics Education and Research, 2026)
Term loans play a crucial role in improving the standard of living by enabling individuals to purchase homes, vehicles, and pursue higher education. In rapidly developing urban regions such as Navi Mumbai, demand for personal loans has increased significantly due to population growth, real estate expansion, and rising educational aspirations. This study presents a descriptive analysis of term loan services offered by selected nationalized banks operating in Navi Mumbai—namely State Bank of India, Bank of Baroda, Union Bank of India, Indian Bank, and Bank of India. The study is entirely based on secondary data collected from official bank websites and government publications. It focuses exclusively on housing loans, vehicle loans, and education loans. The findings reveal that while the basic structure of personal loans remains similar across banks, differences exist in loan variety, customer focus, and service accessibility.